THE CURRICULUM CHANGES IN MADRASAH: META-ANALYSIS AND SYSTEMIC REVIEW - Suwenti, Reni; Tarihoran, Naf’an; Nugraha, Enung (Yayasan Education and Social Center, 2025)
Curriculum changes in madrasas are a phenomenon that continues to develop along with the demands of modern education. This study employs a meta-analysis and systematic review methodology to assess the efficacy of curriculum modifications and the factors that affect them. Data were gathered from multiple studies published between 2020 and 2024 utilizing the PRISMA methodology to guarantee transparency and precision in the analysis. The study's findings indicate that modifications to madrasa curricula positively influence student learning outcomes; however, their efficacy is contingent upon teacher preparedness, policy backing, and resource accessibility. Elements such as the leadership of madrasah principals, educational regulations, and infrastructure preparedness contribute to effective implementation. Furthermore, educators encounter obstacles in adapting to the Merdeka Curriculum, which offers flexibility in the learning process. The research underscores the necessity of a more comprehensive implementation strategy, which should include implementing rigorous regulations and providing extensive teacher training to ensure that curriculum changes in madrasas are implemented sustainably and optimally.